Anharmonic vibrational frequency shifts upon interaction of phenol+ with the open shell ligand O2. The performance of DFT methods versus MP2 - Kocevski, Vancho; Pejov, Ljupčo (American Chemical Society (ACS), 2012)
Anharmonic vibrational frequency shifts of the phenol(+) O-H stretching mode upon complex formation with the open-shell ligand O(2) were computed at several DFT and MP2 levels of theory, with various basis sets, up to 6-311++G(2df,2pd). It was found that all DFT levels of theory significantly outperform the MP2 method with this respect. The best agreement with the experimental frequency shift for the hydrogen-bonded minimum on the potential energy surfaces was obtained with the HCTH/407 functional (-93.7 cm(-1) theoretical vs -86 cm(-1) experimental), which is a significant improvement over other, more standard DFT functionals (such as, e.g., B3LYP, PBE1PBE), which predict too large downshifts (-139.9 and -147.7 cm(-1), respectively). Good agreement with the experiment was also obtained with the mPW1B95 functional proposed by Truhlar et al. (-109.2 cm(-1)). We have attributed this trend due to the corrected long-range behavior of the HCTH/407 and mPW1B95 functionals, despite the fact that they have been designed primarily for other purposes. MP2 method, even with the largest basis set used, manages to reproduce only less than 50% of the experimentally detected frequency downshift for the hydrogen-bonded dimer. This was attributed to the much more significant spin contamination of the reference HF wave function (compared to DFT Kohn-Sham wave functions), which was found to be strongly dependent on the O-H stretching vibrational coordinate. All DFT levels of theory outperform MP2 in the case of computed anharmonic OH stretching frequency shifts upon ionization of the neutral phenol molecule as well. Besides the hydrogen-bonded minimum, DFT levels of theory also predict existence of two other minima, corresponding to stacked arrangement of the phenol(+) and O(2) subunits. mPW1B95 and PBE1PBE functionals predict a very slight blue shift of the phenol(+) O-H stretching mode in the case of stacked dimer with the nearly perpendicular orientation of oxygen molecule with respect to the phenolic ring, which is entirely of electrostatic origin, in agreement with the experimental observations of an additional band in the IR photodissociation spectra of phenol(+)-O(2) dimer [Patzer, A.; Knorke, H.; Langer, J.; Dopfer, O. Chem. Phys. Lett. 2008, 457, 298]. The structural features of the minima on the studied PESs were discussed in details as well, on the basis of NBO and AIM analyses.